Pengaruh Penambahan Ampas Kopi Sebagai Adsorben Pada Limbah Cair Tenun Ikat - Clarita Vikanova Seli; Kristina Tresia Leto; Kartini Rahman Nisa (Journal Innovation In Education, 2024)
Synthetic dyes contain naphthol dyes, one of which contains Cr metal. tie woven wastewater treatment can be carried out using adsorption methods, one of which is using activated charcoal. This study aims to determine the effect of using coffee grounds as an adsorbent on woven textile waste. The method in this study is an experimental method in the form of Posttest Only Control Group Design. The test parameters include the degree of acidity (pH), organoleptic test, and Chromium (Cr) content test. The results showed that the pH test before contact with activated charcoal had a pH value of 5 (acid), after contact with activated charcoal the pH value became 7 (neutral). Thus, the pH value can be said to meet the quality standards of tie-weaving liquid waste. Meanwhile, in organoleptic testing, there was a change in color from black waste to clear yellow. Whereas in testing the Cr level before contact with activated charcoal reached 4.60 mg/l after the addition of a dose of activated charcoal the Cr level decreased to 0.46 mg/l, 0.22 mg/l, and 0.38 mg/l. The effectiveness of the adsorbent ability of the Cr content test in each treatment (P1, P2, P3), still meets the requirements for the quality standard of woven textile wastewater from Cr metal dyes, SNI No 06-6989-22-2004, it can be concluded that the addition of coffee grounds has an effect on of textile woven wastewater.